2022
DOI: 10.1093/ehjcvp/pvac017
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced skin reactions of cardiovascular drugs—a systematic review

Abstract: Purpose This systemic review aims to provide a practical overview of the prevalence, clinical manifestation, and management of adverse photo-induced skin reactions caused by frequently used cardiovascular drugs and to assess their potential relevance for skin cancer development. Methods Data search included PubMed, Web of Science, and the Cochrane Library. A systematic review of peer-reviewed studies reporting the photosensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 89 publications
2
5
0
Order By: Relevance
“…24,25 Thiazides and ACE inhibitors have been associated with an increased risk of NMSC. 26,27 In agreement with our findings, previous studies have suggested that tumor risk may be increased by antihypertensive drugs, particularly hydrochlorothiazide, owing to its photosensitizing properties. 28 Finally, while no studies showed evidence of an association between omeprazole use and BCC risk, omeprazole is included among the photosensitizing drugs which could explain this relationship.…”
Section: Discussionsupporting
confidence: 93%
“…24,25 Thiazides and ACE inhibitors have been associated with an increased risk of NMSC. 26,27 In agreement with our findings, previous studies have suggested that tumor risk may be increased by antihypertensive drugs, particularly hydrochlorothiazide, owing to its photosensitizing properties. 28 Finally, while no studies showed evidence of an association between omeprazole use and BCC risk, omeprazole is included among the photosensitizing drugs which could explain this relationship.…”
Section: Discussionsupporting
confidence: 93%
“…Several case reports describe phototoxic reactions in HCT treated patients [24]. It is important to emphasize, however, that these adverse cutaneous reactions can occur following almost any drug therapies, apart from HCT [1]. Therefore, phototoxic reactions to HCT appear to be individual reactions (possibly by photoallergy) and the majority of individuals treated with HCT do not experience adverse side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The thiazide-diuretic hydrochlorothiazide (HCT) is commonly used in the management of hypertension and heart failure [2][3][4]. Ever since its introduction in the 1950 s, HCT has been suspected to increase photosensitivity, leading to adverse cutaneous reactions in susceptible individuals [1,5]. Recently, pharmacoepidemiologic case-control studies associated the longterm use of HCT with increased rates of skin cancer, such as basal cell carcinoma and squamous cell carcinoma [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amiodarone is a class III antiarrhythmic drug used in cardiovascular diseases such as supraventricular and ventricular arrhythmias [ 98 , 143 ]. Some studies have suggested that phototoxic reactions affect up to 75 % of patients on long-term amiodarone therapy [ 144 , 145 ], while one recent prospective study in a French population reported an incidence rate of less than 10 % [ 112 ].…”
Section: Phototoxic Drugsmentioning
confidence: 99%